Effect of Sorption on Mineralization of Low Concentrations of Aromatic Compounds in Lake Water Samples - Subba-Rao, R. V. (1982)
Montmorillonite-benzylamine complexes were formed immediately upon addition of 20 pg to 20 μg of amine per ml of suspensions containing the clay. The extent of amine sorbed was a linear function of equilibrium amine concentration in lake water. Increases in the clay concentration decreased the percentage of the organic compound that was mineralized at amine levels of 20 pg to 200 ng, but not at 20 μg/ml. A larger percentage of the chemical was released from the complex during mineralization in the presence of high clay concentrations than in the presence of low clay concentrations. The rates of desorption and mineralization increased linearly with benzylamine levels up to 200 ng/ml. Montmorillonite did not enhance mineralization rates at amine levels of 200 ng/ml or lower, but it was stimulatory at 20 μg/ml. Except at high amine and clay concentrations, mineralization was more rapid than desorption during the early periods of decomposition when the amine concentration in solution was relatively high. However, relative to the microbial demand, desorption was more rapid during later periods of decomposition when the amine level in solution was very low. Mineralization of benzoate was not usually affected by montmorillonite, kaolinite, or glass beads. More than 90% of the carbon from benzylamine and benzoate was often mineralized when the substrate concentration was 250 ng/ml or less. After incubation of the chemical in lake water, none of the radioactivity from benzylamine was in the particulate fraction containing natural sediment and microbial cells. The data indicate that clay may have a significant effect on the microbial decomposition of low concentrations of certain organic compounds.